Prospective Study of a Point-of-Care Diagnostic Test for Acute Kidney Injury in a South Asian Hospital - Tejashree S. Gopal; Katherine Xu; Yechiel Muller; Jai Radhakrishnan; Vivekanandan Pillai; Jonathan Barasch; Sreejith Parameswaran; Catherine S. Forster (Kidney International Reports)
Introduction: Serum creatinine (SCr) is used to diagnose acute kidney injury (AKI) but has limited utility to distinguish volume depletion from tubular injury. Urine neutrophil gelatinase-associated lipocalin (uNGAL) distinguishes these causes of elevated SCr. Methods: We tested a novel point-of-care (POC) dipstick to measure uNGAL at presentation at the emergency medical services department (EMSD) in a tertiary care hospital in Puducherry, India. The primary outcome was a sustained elevation of SCr; the secondary outcome was in-hospital mortality. The study enrolled 396 patients with a mean age of 49.7 years (SD: 16); 36% were female. Sufficient measurements for SCr kinetics were obtained from 229 patients. Owing to inconsistent serial measurements of SCr for some patients, subanalyses were conducted for “strict” and “inclusive” SCr defined subsets, which yielded similar results. Results: Elevated uNGAL (median [interquartile range]: 500 ± 350 ng/ml) in the EMSD indicated sustained increases of SCr (> 48 hours); whereas much lower levels of uNGAL indicated either transient changes (< 48 hours; 150 ± 250 ng/ml) or no elevation of SCr (50 ± 97.5 ng/ml) (P < 0.01). Analysis of the entire cohort (N = 229) or the “strict” subset with complete SCr measurements (n = 129) (P < 0.01) yielded similar data. uNGAL was highly specific and moderately sensitive (specificity: 0.90 [0.83–0.95]; sensitivity: 0.82 [0.67–0.96]) to indicate sustained elevation of SCr (area under the curve–receiver operating characteristic curve: 0.86; confidence interval: [0.76–0.96] and odds ratio [OR]: 16.19; confidence interval: [5.63–59.02] for NGAL levels > 125 ng/ml). Elevated uNGAL was also associated with mortality (OR: 3.91 [confidence interval: 2.17–7.33]). uNGAL, infection, and proteinuria demonstrated limited correlations (R2 = 0.26; P < 10−36). Conclusion: uNGAL dipstick can diagnose kidney damage associated with sustained elevation of SCr and death at patient encounter in the EMSD.